New evidence disclosed for the engineered strong interfacial interaction of graphene/rubber nanocomposites. (2nd June 2017) - Xie, Zheng-Tian; Fu, Xuan; Wei, Lai-Yun; Luo, Ming-Chao; Liu, Yu-Hang; Ling, Fang-Wei; Huang, Cheng; Huang, Guangsu; Wu, Jinrong
Abstract: Interfacial interaction is of crucial importance for polymer nanocomposites. To improve interfacial interaction between graphene (GE) and isoprene rubber (IR), we grafted a silane coupling reagent, (bis-[γ-(triethoxysilyl) propyl]-etrasulfide), onto graphene oxide (GO). The modified GO was mixed with IR by solution blending and then reduced in situ to prepare IR/surface modified GE nanocomposites (IR/SGE). Raman mapping illustrates that the bound rubber on SGE is much thicker than that on unmodified GE, suggesting a strong interfacial interaction between SGE and IR. As a result, IR/SGE shows slower chain dynamics and lower strain-induced crystallinity than IR/GE. However, on-line Raman measurements show that the G band of IR/SGE shifts more noticeably during uniaxial tensile deformation than that of IR/GE; this suggests more efficient load transfer between SGE and IR. Consequently IR/SGE has better mechanical properties than IR/GE. Graphical abstract: Highlights: Interfacial interaction of IR/SGE composite was significantly enhanced by modifying GE with BTESPT. The thicker bound rubber of IR/SGE composite was observed by Raman mapping. IR/SGE shows slower chain dynamics and strain-induced crystallization rate than IR/GE. More efficient load transfer leads to superior mechanical properties of IR/SGE composite.